1984
DOI: 10.1126/science.6203171
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Bleomycin Lethality by Anticalmodulin Drugs: A Role for Calmodulin in DNA Repair

Abstract: Treatment of exponentially growing Chinese hamster ovary cells with bleomycin causes a dose-dependent decrease in cell survival due to DNA damage. This lethal effect can be potentiated by the addition of a nonlethal dose of the anticalmodulin drug N-(4-aminobutyl)-5-chloro-2-naphthalenesulfonamide ( W13 ) but not its inactive analog N-(4-aminobutyl)-2-naphthalenesulfonamide ( W12 ). By preventing the repair of damaged DNA, W13 also inhibits recovery from potentially lethal damage induced by bleomycin. These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 14 publications
2
37
0
1
Order By: Relevance
“…We found that HT treatment (even for non-toxic exposures of 30min at 44°C) restricts the access of active drug to DNA. This observation is consistent with the notion that an increase in nuclear protein in HT-treated cells reduces the accessibility of DNA (Roti Roti, 1982) and the observation (Braun & Hahn, 1975) Chafouleas et al, 1984) after BLM removal would only monitor effects on a restricted class of lesions. Consequently we have adopted the approach that changes in the levels of BLM-induced DNA damage for simultaneous exposures to HT and TFP, effectively monitor the capacity of rapair processes to limit lesion accumulation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that HT treatment (even for non-toxic exposures of 30min at 44°C) restricts the access of active drug to DNA. This observation is consistent with the notion that an increase in nuclear protein in HT-treated cells reduces the accessibility of DNA (Roti Roti, 1982) and the observation (Braun & Hahn, 1975) Chafouleas et al, 1984) after BLM removal would only monitor effects on a restricted class of lesions. Consequently we have adopted the approach that changes in the levels of BLM-induced DNA damage for simultaneous exposures to HT and TFP, effectively monitor the capacity of rapair processes to limit lesion accumulation.…”
Section: Discussionsupporting
confidence: 78%
“…Calmodulin is a relatively low molecular mass, acidic calcium binding protein which is uniquitous amongst eukaryotic cells. Apart from its apparent importance in the control of cell proliferation (for review see Means et al, 1982) there is recent evidence that calmodulin may have a role in DNA repair given the capacity of calmodulin inhibitors to inhibit the repair of bleomycin induced DNA ©) The Macmillan Press Ltd., 1986 damage (Chafouleas et al, 1984) and UV-induced pyrimidine dimers (Charp & Regan, 1985).…”
mentioning
confidence: 99%
“…An important factor that governs tumor cell responsiveness to bleomycin is the cellular DNA DSB repair capacity, and, in line with this, increased sensitivity to bleomycin is observed in cells deficient in NHEJ (15,23,24). TFP, a phenothiazine class antipsychotic drug, has been reported to enhance bleomycin-induced cytotoxicity by a poorly characterized mechanism (2,4,5,22). We have previously shown that TFP can inhibit the kinase activity of the NHEJ core component DNA-PK in vitro (17).…”
Section: Discussionmentioning
confidence: 97%
“…Phenothiazines are well-characterized calmodulin antagonists (26,27), and this led Chafouleas et al (2) to propose that TFP might augment bleomycin cytotoxicity by inhibiting a putative calmodulin-regulated DNA repair pathway. Recent studies have shown that inositol phosphates serve as cofactors for DNA-PK cs during NHEJ (28 -30).…”
Section: Discussionmentioning
confidence: 99%
“…Among its many functions, CaM has been shown to be involved in cell proliferation [2], DNA repair [3] and gene expression [4]. In addition, CaM binds to several nuclear proteins [5].…”
Section: Introductionmentioning
confidence: 99%